2005
DOI: 10.1093/carcin/bgi267
|View full text |Cite
|
Sign up to set email alerts
|

Associations between GPX1 Pro198Leu polymorphism, erythrocyte GPX activity, alcohol consumption and breast cancer risk in a prospective cohort study

Abstract: Breast cancer may be related to oxidative stress. Breast cancer patients have been reported to have lower antioxidant enzyme activity than healthy controls and the polymorphism GPX1 Pro198Leu has been associated with risk of lung and breast cancer. The purpose of the present nested case-control study was to determine whether GPX1 Pro198Leu and glutathione peroxidase (GPX) activity in prospectively collected blood samples are associated with breast cancer risk among postmenopausal women and whether GPX activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
2
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(197 citation statements)
references
References 35 publications
15
167
2
9
Order By: Relevance
“…It has been determined that individuals who used to smoke are at two times more risk to develop bladder cancer than individuals that never smoke (OR = 2.3; 95% CI 1.28-4.07; p<0.05). These findings are supported because it has previously been reported that smoking results in lower GPX activity (Ravn-Haren, et al, 2006). As a result of the ethnic differences, the distribution of the polymorphisms is affected; some studies have found that the risk of developing bladder cancer when a significant incidence of the L/L allelic variant exists, with the proportion of homozygous individuals for the L/L allele being low for the Asian population and high for the Caucasian population (Ichimura, et al, 2004;Hu & Diamond, 2003).…”
Section: Resultssupporting
confidence: 83%
“…It has been determined that individuals who used to smoke are at two times more risk to develop bladder cancer than individuals that never smoke (OR = 2.3; 95% CI 1.28-4.07; p<0.05). These findings are supported because it has previously been reported that smoking results in lower GPX activity (Ravn-Haren, et al, 2006). As a result of the ethnic differences, the distribution of the polymorphisms is affected; some studies have found that the risk of developing bladder cancer when a significant incidence of the L/L allelic variant exists, with the proportion of homozygous individuals for the L/L allele being low for the Asian population and high for the Caucasian population (Ichimura, et al, 2004;Hu & Diamond, 2003).…”
Section: Resultssupporting
confidence: 83%
“…In our study, we did not find an overall relationship between GPX1 Pro200Leu polymorphism and prostate cancer. The C allele of GPX1 has been associated with an increased risk of breast (30), bladder (31), and lung cancer (21), but other studies, including breast, have found no associations (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…GPX1, the first identified and the most abundant selenoprotein in mammals (Kiss et al 1997), is ubiquitously expressed in humans, protecting cells against oxidative damage by reducing hydrogen peroxide and a wide range of organic peroxides (Arthur 2000). A SNP resulting in a proline-leucine substitution at codon 198 of human GPX1 has been identified and has been associated with increased risk of breast (Ravn-Haren et al 2006), prostate (ArsovaSarafinovska et al 2008), lung (Raaschou-Nielsen et al 2007), and bladder cancer (Ichimura et al 2004) but is not consistent in all populations (Ahn et al 2005;Cebrian et al 2006;Udler et al 2007).…”
Section: Polymorphisms In Antioxidant Genesmentioning
confidence: 99%